2016
DOI: 10.4314/sajas.v46i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oregano essential oil and attapulgite on growth performance, intestinal microbiota and morphometry in broilers

Abstract: Two experiments were conducted to study the effects of a blend of oregano essential oil (OEO) (as a source of natural antibacterial growth-promoting substances) and attapulgite (as a source of toxin-binder and as an antidiarrhoeal agent) on growth performance, intestinal microbiota, and intestinal morphometry in broiler chickens (Ross-308). In the first trial, the control group was fed a basal diet without antibiotic growth promoters, and the experimental group was fed the basal diet supplemented with 5% OEO (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 35 publications
0
20
1
1
Order By: Relevance
“…Contrary to results in the current study, Skoufos et al (2016) did not find any differences in BW of 28-d-old broilers fed0 or 15 mg oregano essential oil (OEO)/kg feed. Peng et al (2016) obtained higher BW in broilers fed 300 and 600 mg OEO /kg diet in the grower (1-21 d) and finisher (22-42 d) phases, which are similar to results observed in the current study with 200 to 1000 mg MOO/kg.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to results in the current study, Skoufos et al (2016) did not find any differences in BW of 28-d-old broilers fed0 or 15 mg oregano essential oil (OEO)/kg feed. Peng et al (2016) obtained higher BW in broilers fed 300 and 600 mg OEO /kg diet in the grower (1-21 d) and finisher (22-42 d) phases, which are similar to results observed in the current study with 200 to 1000 mg MOO/kg.…”
Section: Discussioncontrasting
confidence: 99%
“…The null hypothesis (MOO treatment effects on breast meat quality are equal to the no-MOO control treatment) is based on the p-value according to a significance level determined atα = 0.05. Several studies have evaluated oregano essential oil supplementation at various levels (mg/kg) in feed: 300 (Alp et al, 2012;Skoufos et al, 2016), 65 (Bozkurt et al, 2012;Sun et al, 2015), 125 (Hong et al, 2012), 0, 60, 100 and 200 (Hashemipour et al, 2013), 15-60 (Khattak et al, 2014), 250 (Ghazi et al, 2015), 300 and 500 (Mohiti-Asli & Ghanaatparast-Rashti, 2015), 400-1600 (Silva Vazquez et al, 2015), 300 and 600 (Peng et al, 2016) and 400 (Méndez-Zamora et al, 2017). These studies obtained significant effects with all the OEO levels evaluated in broilers regarding, for example, BW, FI and FCR.…”
Section: Discussionmentioning
confidence: 99%
“…Brenes and Roura (2010) and Hippensteil et al (2011) reported that the essential oils of certain herbs, can show positive effects in performance, but show no consistency in feed intake when supplemented to diets between 12 and 300 ppm. In previous studies, the use of oregano (herb or its major compounds) alone or in combination with benzoic acid were examined as candidate replacers of antibiotic growth promoters with controvertial results (Langhout, 2000;Symeon et al, 2009;Symeon et al, 2010;Giannenas et al, 2013Giannenas et al, , 2014aGiannenas et al, , 2014bGiannenas et al, , 2016bSkoufos et al, 2016). Dietary supplementation with oregano essential oil, attapulgite, benzoic acid or their mixture did not alter the protein and fat content of breast and thigh meat of broiler chickens, although higher levels of phenolic compounds were noticed in the groups fed oregano essential oil that could increase its antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve optimal production targets, particularly during the summer months, the temperature of the shed must be maintained in a narrow range of 18 °C to 22 °C, which is costly (Yoo et al, 2016). Antibiotics were utilized in the poultry industry to reduce the adverse effects of environmental stress, but their use in animal feed was banned by the EU in 2006 (Skoufos et al, 2016). Therefore, many studies have explored dietary supplements that could not only improve the gut health of birds, but also replace growth promoting antibiotics.…”
Section: Discussionmentioning
confidence: 99%